Academic Emotional Learning: A Critical Component of Self-Regulated Learning in the Emotional Learning Cycle. Issue 2 (3rd April 2019) - Ben-Eliyahu, Adar
Abstract : The aim of this article is to map the academic emotional learning cycle from a theoretical and practical perspective through the lens of self-regulated learning. Focusing on the learner, a further iteration of the emotional dimension of the integrated self-regulated learning model is articulated by considering within-individual components (i.e., the intraindividual system). Academic emotions are considered an important component of learning that, along with intellectual behavioral-cognitive goals, should be explicit targets of learning. An emotional learning cycle is presented, according to which broader affective inclinations––the expectation to experience certain affect or emotion––shape the relations between emotions and self-regulated emotions that occur during a learning episode. Strategies for self-regulated emotions are outlined in light of the need for more research in this field, along with proposed future directions for research and educational implications.